ANALISIS KINERJA VACUUM CIRCUIT BREAKER PADA SISI 13,8 kV PT PAITON OPERATION & MAINTENANCE INDONESIA (POMI) UNIT 3 - Adityara, Farrel Billy; Dhofir, Moch.; Hasanah, Rini Nur; Siswandi, Wawan (Jurnal Mahasiswa TEUB, 2024)
This study aims to analyze the performance of the VCB based on the parameters in SPLN Standard No. 52-1 1983 and IEC 62271-100 and to determine the technical feasibility of the 13,8 kV VCB work at PT POMI Unit 3A is still feasible to operate or not. The VCB parameter test uses standards on each test with the parameters of insulation resistance, contact resistance, synchronous contact, and vacuum. This study was conducted by comparing the data of the test results in 2015 and 2021 with the standard values in each test. In the insulation resistance test results obtained at each measuring point, each phase has a value above 13,8 MΩ. The contact resistance test results of each phase obtained have a value below 22 μΩ. In the synchronous contact test, the results of calculating the delta time or the difference in working time when VCB Open and VCB Close have a value below 10 ms. The results of vacuum testing of each phase on the test equipment indicator show an indication of "GOOD" which means that the pressure in the VCB has a value below 10-7 mbar. Based on the test results of insulation resistance, contact resistance, synchronous contact, and vacuum, the VCB 13,8 kV PT POMI Unit 3A Incoming is in a suitable condition for use and can be operated because the test results according to standards. Keywords – Vacuum Circuit Breaker (VCB), Insulation Resistance, Contact Resistance, Synchronous Contact, Vacuum.